Male C57BL6/N and C57BL6/J Mice Respond Differently to Constant Light and Running-Wheel Access - Capri, Kimberly M.; Maroni, Marissa J.; Deane, Hannah V.; Concepcion, Holly A.; DeCourcey, Holly; Logan, Ryan W.; Seggio, Joseph A. (Frontiers in Behavioral Neuroscience, 2019)
Previous studies have shown that exposure to circadian disruption produces negative effects to overall health and behavior. More recent studies illustrate that strain differences in the behavioral and physiological responses to circadian disruption exist, even if the strains have similar genetic backgrounds. As such, we investigated the effects of constant room-level light (LL) with running-wheel access on the behavior and physiology of male C57BL6/J and C57BL6/N mice. Mice were exposed to either a 12:12 LD cycle or LL and given either a standard home cage or a cage with a running-wheel and their response to behavioral assays (open-field, light-dark box, novel object) and measures of metabolism were observed. Under standard conditions, C57BL6/Js exhibited increased locomotor activity and reduced anxiety compared to C57BL6/Ns. C57BL6/Js had greater period lengthening and increased anxiety, while C57BL6/Ns exhibited increased weight gain in LL and had no increase in anxiety in LL. C57BL6/Js also decreased exploration with running-wheel access while C57BL6/Ns did not. These results show that the different C57BL/6 strains exhibit different behavioral and physiological responses to circadian disruption and wheel-running access.